Subprime Crisis Revisited: Effect of Payment Shock on Foreclosure Rates - Kelly, Lynne; Lindsey-Taliefero, Debby (Journal of Applied Business and Economics, 2024)
This study investigates how payment shock from interest rate resets affects subprime mortgage foreclosure rates. Using robust econometric techniques (OLS, 2SLS, GMM), it isolates the causal effect of payment shock while accounting for house prices and borrowers’ ability to pay. Our findings show a significant positive link (27%) between payment shock and foreclosure rates. It highlights economic stability’s importance, showing negative correlations between foreclosure rates and ability to pay, as well as foreclosure rates and house prices. Lagged foreclosure rates show a persistent effect. The GMM model provides the most reliable estimates by addressing endogeneity, heteroscedasticity, and serial correlation.